2017
DOI: 10.1016/j.matbio.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Embryo implantation triggers dynamic spatiotemporal expression of the basement membrane toolkit during uterine reprogramming

Abstract: Basement membranes (BMs) are specialized extracellular scaffolds that influence behaviors of cells in epithelial, endothelial, muscle, nervous, and fat tissues. Throughout development and in response to injury or disease, BMs are fine-tuned with specific protein compositions, ultrastructure, and localization. These features are modulated through implements of the BM toolkit that is comprised of collagen IV, laminin, perlecan, and nidogen. Two additional proteins, peroxidasin and Goodpasture antigen-binding pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 99 publications
(133 reference statements)
0
18
0
Order By: Relevance
“…The following primary antibodies were applied to the sections: rat anti-collagen IV NC1 (1:500 dilution, JK2, were from Y. Sado, Shigei Medical Research Institute, Okayama, Japan [5], [6]), rabbit anti-laminin (1:50 dilution for tissues not treated with dissociation buffer and 1:500 dilution for those that were pre-treated with dissociation buffer, ab11575, Abcam, Cambridge, MA), rabbit anti-peroxidasin (1:250 dilution, were from G. Bhave, Vanderbilt University, Nashville, TN [7]), Alexa546 conjugated mouse anti-GPBP (1:50 dilution, mAb N26 to the N-terminal serine-rich domain conserved across all GPBP isoforms in several species [8], from Fibrostatin, SL, Valencia, Spain), and Alexa546 conjugated mouse anti-GPBP-1 (1:50 dilution, mAb e11-2 to the 26-amino acid residue of exon 11 not present in GPBP-2, also called CERT [9], from Fibrostatin, SL, Valencia, Spain). A previously described dissociation buffer was used on sections co-stained with collagen IV antibody (JK2) [1], [5] followed by several washes with PBS and PBS/0.2% Tween. Detection and co-detection with GPBP antibodies (mAbs N26 and e11-2) were performed without dissociation treatment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following primary antibodies were applied to the sections: rat anti-collagen IV NC1 (1:500 dilution, JK2, were from Y. Sado, Shigei Medical Research Institute, Okayama, Japan [5], [6]), rabbit anti-laminin (1:50 dilution for tissues not treated with dissociation buffer and 1:500 dilution for those that were pre-treated with dissociation buffer, ab11575, Abcam, Cambridge, MA), rabbit anti-peroxidasin (1:250 dilution, were from G. Bhave, Vanderbilt University, Nashville, TN [7]), Alexa546 conjugated mouse anti-GPBP (1:50 dilution, mAb N26 to the N-terminal serine-rich domain conserved across all GPBP isoforms in several species [8], from Fibrostatin, SL, Valencia, Spain), and Alexa546 conjugated mouse anti-GPBP-1 (1:50 dilution, mAb e11-2 to the 26-amino acid residue of exon 11 not present in GPBP-2, also called CERT [9], from Fibrostatin, SL, Valencia, Spain). A previously described dissociation buffer was used on sections co-stained with collagen IV antibody (JK2) [1], [5] followed by several washes with PBS and PBS/0.2% Tween. Detection and co-detection with GPBP antibodies (mAbs N26 and e11-2) were performed without dissociation treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The sections were stained with uranyl acetate and Reynold lead citrate before they were imaged at 30,000x on an electron microscope (Philips T-12 equipped with an AMT CCD camera system, FEI, Hillsboro, OR). Further details of immunofluorescence and electron microscopy methods are available in the accompanying research article [1].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins include collagen IV, laminin, nidogen, and agrin/perlecan (17)(18)(19). Recently, additional proteins were identified: peroxidasin (20), lysyl oxidase II (21), and Goodpasture antigen-binding protein (GPBP) (22)(23)(24). Recent studies in nonbilaterian animals have shown that collagen IV and laminin (25) are the earliest components of basement membrane, as evidenced in ctenophores and sponges, the two oldest animal lineages, and were likely essential for animal multicellularity (2,3).…”
mentioning
confidence: 99%
“…Among BM proteins, GPBP was uniquely poised to also play a role in the appearance of BMs and the transition to multicellularity, owing to its multiple isoforms (23,26,27) with varied functions both inside (28,29) and outside of cells (22)(23)(24)30).…”
mentioning
confidence: 99%